Critérios de divisibilidade: usuais, incomuns e curiosos - Silva, Talysson Paulo da (2019)
The criterion of divisibility is known by students and some teachers as simples "tricks" . They facilitate the resolution of exercises and avoid the use of multiple accounts, however this subject in essence brings a rich and deep arithmetic. We deal with this work on the criterion of common divisibility, those that one learns in basic education and other unpublished ones. Algebra and Arithmetic , such as: Well - Ordering Principle (PGO) , Principle of Mathematical Induction (PMI) , Euclidean division, divisibility, primary numbers , Euclides algorithm , diophantine equations, decimal system and modular arithmetic. After , we present, demonstrate and exemplify the most common divisibility criterion, seeking the reader’s interest in knowledge. We finished with the creation, demosntration and exemplification of the most sophisticated criterion of divisibility.